Use of geostatistics sustainable management of galls nematoides of coffee tree - Almeida, Leandro da Silva; Guimarães, Ednaldo Carvalho (Coffee Science - ISSN 1984-3909, 2017)
Phytonematoids are one of the main causes of losses in coffee cultivation. This work aimed to use geostatistics as a tool for spatial mapping of phytonematoids, thus seeking the sustainable management of these in the properties. The experiment was carried out at farm Brasil, which has 65 ha of arabica coffee (Coffea arabica L.), located in the municipality of Araguari-MG, whose geographical coordinates of the headquarters are: 18 ° 32’55.99 “S, 48 ° 24’10.46” W. A non-systematic mesh of one point per hectare was used, totaling 65 points. The species of phytonematoids identified was Meloidoigyne exigua, which were evaluated for the probability of infestation in the area and its linear economic damage, through indicator kriging. It was verified that the geostatistical models were appropriate to describe the spatial behavior of the phytonematoids. It was also possible to visualize the greater risks of infestations and infestation-free areas, thus allowing the planning of the activities of the property in order to avoid the increase of infestation in the area and also to direct the application of inputs (chemical or biological) Areas where control would be required.